State and Trends of Carbon Pricing 2020 - World Bank (Washington, DC: World Bank, 2020)
This report provides an up-to-date overview of existing and emerging carbon pricing instruments around the world, including international, national and subnational initiatives. It also investigates trends surrounding the development and implementation of carbon pricing instruments and how they could accelerate the delivery of long-term mitigation goals. Specifically, this includes the use of carbon taxes, emissions trading systems and crediting mechanisms. International cooperation on carbon pricing and the status of work surrounding Article 6 of the Paris Agreement is also canvassed.